Non-Financial Performance Indicators and Corporate Burnout: A Narrative Review - Haryanto, Haryanto; Nurdiniah, Dade; Putri, Sri Yuli Ayu (International Journal of Business, Law, and Education, 2025)
Corporate burnout has emerged as a critical challenge in modern workplaces, particularly in organizations struggling to achieve a sustainable work-life balance. This study explores the role of management accounting in mitigating burnout through the integration of non-financial performance indicators (NFPIs), strategic budgeting for employee well-being, and workload optimization models. Adopting a narrative review approach, this research synthesizes insights from scholarly literature on management accounting, corporate governance, and occupational well-being. Anchored in Stakeholder Theory and Contingency Theory, the study highlights how organizations incorporating NFPIs into performance management frameworks experience reduced employee stress, improved retention rates, and enhanced operational efficiency. However, significant barriers—such as corporate resistance, measurement complexities, and leadership inertia—hinder the widespread adoption of well-being-focused accounting strategies. The findings contribute to the evolving role of management accounting in human capital sustainability, emphasizing the need for accounting professionals and business leaders to integrate burnout prevention metrics into financial decision-making. This study also outlines practical recommendations for embedding employee-centric financial planning models within corporate governance structures. By bridging the gap between financial and well-being metrics, the study offers a roadmap for future research on the intersection of management accounting and workplace sustainability.